2021
DOI: 10.3390/en14123640
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modelling of LNG Powered Combined Energy Systems in Port Areas

Abstract: Liquefied Natural Gas (LNG) is a crucial resource to reduce the environmental impact of fossil-fueled vehicles, especially with regards to maritime transport, where LNG is increasingly used for ship bunkering. The present paper gives insights on how the installation of LNG tanks inside harbors can be capitalized to increase the energy efficiency of port cities and reduce GHG emissions. To this purpose, a novel integrated energy system is introduced. The Boil Off Gas (BOG) from LNG tanks is exploited in a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The literature review indicates that many studies have been conducted on ports from multiple perspectives such as berth optimization [23,24,30,31], logistics scheduling [36,38], and energy supply [5,6]. However, there is still relatively little research on the collaborative optimization of logistics and energy systems.…”
Section: Literature Analysis and Motivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review indicates that many studies have been conducted on ports from multiple perspectives such as berth optimization [23,24,30,31], logistics scheduling [36,38], and energy supply [5,6]. However, there is still relatively little research on the collaborative optimization of logistics and energy systems.…”
Section: Literature Analysis and Motivationsmentioning
confidence: 99%
“…Their experiment found that the "operation surface" scheduling mode shortened the average waiting time by 33% compared to the "operation line" scheduling mode. Borelli et al [23] use the lowest cost of delay to minimize the total ship service time by considering berth productivity under a given berth schedule. Aljuaid et al [24] adopt a mixed-integer linear programming model, aiming to minimize the waiting time of ships at ports and improve the efficiency of ship entry and exit.…”
Section: Introductionmentioning
confidence: 99%
“…Despite proving effective at reducing air pollution [30,31] these methods are not widespread, and the majority of world ports do not implement them. Shore-to-ship power, also known as alternative marine power, shore power or cold ironing, is the practice of providing an electricity supply to ships in port.…”
Section: Air Pollutionmentioning
confidence: 99%